Cultural struggles : performance, ethnography, praxis - Conquergood, Lorne Dwight, 1949-2004.; Johnson, E. Patrick, 1967- (Ann Arbor : University of Michigan Press, 2013)
"The late Dwight Conquergood's research has inspired an entire gener ation of scholars invested in performance as a meaningful paradigm to u nderstand human interaction, especially between structures of power and the disenfranchised. Conquergood's research laid the groundwork for ot hers to engage issues of ethics in ethnographic research, performance a s a meaningful paradigm for ethnography, and case studies that demonstr ated the dissolution of theory/practice binaries. Cultural Struggles is the first gathering of Conquergood's work in a single volume, tracing the evolution of one scholar's thinking across a career of scholarship, teaching, and activism, and also the first collection of its kind to b ring together theory, method, and complete case studies. The collection begins with an illuminating introduction by E. Patrick Johnson and end s with commentary by other scholars (Micaela di Leonardo, Judith Hamera , Shannon Jackson, D. Soyini Madison, Lisa Merrill, Della Pollock, and Joseph Roach), engaging aspects of Conquergood's work and providing ins ight into how that work has withstood the test of time, as scholars sti ll draw on his research to inform their current interests and methods"- -
Includes bibliographical references and index.
Keywords: Performing arts -- Social aspects; Ethnology -- Philosophy